Rozważania o istocie rzeczywistości = Some ideas on the source of reality - Szyszko-Bohusz, Andrzej (1934- ) (Zielona Góra: Uniwersytet Zielonogórski)
The article consists the authors' opinion on several fundamental questions in the field of the Christian religion as well as oriental religions - Hinduism, Buddhism, Islam. The most important problems are as follows: Creation of the Universe by God, the primordial sin, falling of the first parents, the mystery of the Holy Trinity, Crucifixion, Resurrection, the direct meeting with God, omnipotence of God, problem of the Christian personalism, relation of goodness and evil.
Keywords: God; primordial sin; genetic immortality; Holy Trinity; Crucifixion; Resurrection; Christian personalism; goodness; evil; free-will